Exploring Kv1.2 Channel Inactivation Through MD Simulations and Network Analysis - Costa, Flavio; Guardiani, Carlo; Giacomello, Alberto (Frontiers in Molecular Biosciences, 2021)
The KCNA2 gene encodes the Kv1.2 channel, a mammalian Shaker-like voltage-gated K+ channel, whose defections are linked to neuronal deficiency and childhood epilepsy. Despite the important role in the kinetic behaviour of the channel, the inactivation remained hereby elusive. Here, we studied the Kv1.2 inactivation via a combined simulation/network theoretical approach that revealed two distinct pathways coupling the Voltage Sensor Domain and the Pore Domain to the Selectivity Filter. Additionally, we mutated some residues implicated in these paths and we explained microscopically their function in the inactivation mechanism by computing a contact map. Interestingly, some pathological residues shown to impair the inactivation lay on the paths. In summary, the presented results unveil the microscopic mechanism of inactivation in Kv1.2 channel which is of relevance for the early screening of neuronal mammalian channelopathies.